Ankyloblepharon Filiforme Adnatum in a Newborn Baby Girl - Anggisari Danastri Dharma; Rozalina Loebis (Vision Science and Eye Health Journal, 2022)
Introduction: One type of congenital defect, ankyloblepharon filiforme adnatum (AFA), is characterized by a single or many strands of connective tissue connecting the upper and lower eyelids. It occurs only infrequently at the lateral or medial canthus. The eyelids normally begin to form within the fifth month of pregnancy, and they usually begin to separate entirely into an upper and lower lid by the seventh month of pregnancy. This type of tissue always originates from the grey line, which is located anterior to the meibomian gland orifices and posterior to the cilia. Case presentation: A 22-day-old female child was taken to the Surabaya Eye Clinic with a congenital eye condition. Because his top and lower eyelids were stuck together at birth, she was unable to open his eyes fully. The infant, who weighed 2.8 kg at birth, was delivered by elective caesarean section at 39 weeks gestation to a 28-year-old primigravida mother. There were no abnormalities discovered during the prenatal, intranatal, or postnatal stages. Except for iron and vitamins, the mother is not taking any medications. There was no prior history of X-ray exposure found. There was no history of congenital abnormalities or consanguinity in the patient’s family. Conclusions: Ankyloblepharon filiforme adnatum (AFA) is a rare case. Early diagnostic and comprehensive management including surgical correction should be performed promptly to minimize any risk of amblyopia, and enable full examination of the eye.